PC based Kenwood TS-570D transceiver controller - Airul Sharizli, Abdullah; Mohd Falfazli, Mat Jusof (IEEE, 2011)
This project discuss about the application of the internet as a media for device remote controller. Communication using serial port is also discussed in this study as this method is used for controlling the electric device via local computer. But the main concerned of this study is to develop a remote control application for the KENWOOD TS-570D transceiver using VISUAL BASIC 2008 programming language. This programming language is also used in developing application for the server which will act as the interface between the client and the transceiver. The remote application developed in this project despite all its weakness can be considered as a first step towards creating an even more complex remote control application via the internet.